2014
DOI: 10.1186/1756-0500-7-340
|View full text |Cite
|
Sign up to set email alerts
|

Medical characteristics of the oldest old: retrospective chart review of patients aged 85+ in an academic primary care centre

Abstract: BackgroundThe population aged 85 + − the “oldest old” – is now the fastest growing age segment in Canada. Although existing research demonstrates high health services utilization and medication burden in this population, little clinically derived evidence is available to guide care. This is a descriptive study in a primary care context seeking to describe the most common health conditions and medications used in the “oldest old”.MethodsWe conducted a retrospective chart review of all family practice patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…The median number of co‐morbidities was 7–8 in this cohort of inpatients, which is comparable to a Canadian study of 564 primary care patients among whom those in the 85+ age group experienced, on average, 6.4 concurrent chronic conditions . The patients in this study were also frail, with an FI between 0.45 and 0.47.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The median number of co‐morbidities was 7–8 in this cohort of inpatients, which is comparable to a Canadian study of 564 primary care patients among whom those in the 85+ age group experienced, on average, 6.4 concurrent chronic conditions . The patients in this study were also frail, with an FI between 0.45 and 0.47.…”
Section: Discussionsupporting
confidence: 70%
“…19 The median number of co-morbidities was 7-8 in this cohort of inpatients, which is comparable to a Canadian study of 564 primary care patients among whom those in the 85+ age group experienced, on average, 6.4 concurrent chronic conditions. 20 The patients in this study were also frail, with an FI between 0.45 and 0.47. When the FI is contextualised against clinical descriptors, the Clinical Frailty Scale, this value denotes a group of frail patients who are completely dependent on others for ADL, or are terminally ill. 21 Also, though the majority were admitted from the community, the median length of stay of nearly a month and almost a third requiring discharge for the first time to an RACF reflect the inherent frailty of this population, which did not vary in its magnitude across the age groups.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…reported the clinical characteristics of old‐old patients in Canada and showed that these patients received a mean number of 6.8 medications per day. They suggested that multimorbidity and polypharmacy were highly prevalent in old‐old adults . Hohl et al .…”
Section: Discussionmentioning
confidence: 99%
“…A hipertensão arterial é uma doença multifatorial que pode acarretar graves consequências para o indivíduo, sendo considerada como a causa mais frequente de morbimortalidade nos idosos (OLIVEIRA; MOREIRA, 2010). Tsoi et al (2014) observou, em uma revisão de prontuários médicos realizada no Canadá com pacientes com 85 anos de idade ou mais, que a hipertensão (65%) foi a segunda DCNT mais prevalente na população em estudo, atrás apenas das doenças cardiovasculares (79%).…”
Section: Hipertensão Arterial Prevalênciaunclassified